Implementación de un aparcamiento de bicicleta automático - Guamán Cumbicos, Jorge Ricardo (2024)
The present investigation presents the design of a prototype for automatic bicycle parking, considering the Ecuadorian technical standard INEN 2314, as well as international design construction criteria. This is also known as an automated bicycle parking system, which is a facility designed to park bicycles efficiently and automatically. This concept aims to address space issues and optimize the use of areas designated for bicycle parking, especially in urban environments where space availability can be limited. The design, sizing, and implementation of an outdoor automatic bicycle parking prototype were structured considering the recommendations presented in different bicycle parking systems. A prototype is proposed to park a bicycle, whether conventional or electric. For the design and sizing, the geometry of the bicycle is considered, as well as design methods and models. The prototype proposal includes a security system that facilitates its use through the management of the SpeedFace-V4L biometric control equipment, from which user registration can be controlled. Additionally, through the biometric equipment, the operation of a 12 V DC solenoid electromagnetic lock is controlled, allowing the opening and locking of the prototype's movable part. Key words: cycle-parking, conventional bicycle, electric bicycle.